KEJADIAN OBESITAS PADA REMAJA DAN FAKTOR PENYEBAB - Nilam Noorma; Ria Angelina Jessica Rotinsulu; Auliarinda Noviani; Safrina Safrina (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Obesity is a condition characterized by excessive body fat accumulation resulting from a long-term imbalance between energy intake and energy expenditure. The purpose of this study was to identify the factors causing obesity in adolescents. A cross-sectional study design was used in this research. The study was conducted at SMPN 36 Surabaya in April 2025. The study population consisted of all 11th- and 12th-grade students. The sample comprised 85 respondents. Stratified random sampling was used as the sampling technique. The research instrument used was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated a significant association between physical activity (p-value 0.004) and the prevalence of obesity among adolescents. It is recommended that the school improve its sports facilities and encourage students to be more active through extracurricular activities and regular sports events.Keywords: Physical Activity, Obesity, Adolescents